Difficulties in the teaching and learning process of Differential and Integral Calculus - Macêdo, Josué Antunes; Gregor, Isabela Cristina Soares (Educação Matemática Debate, 2020)
The Differential and Integral Calculus (DIC) course is taught in six of the nine undergraduate courses of the Federal Institute of Education, Science and Technology of the North of Minas Gerais (IFNMG), campus Januária and has a high failure rate compared to other subjects. This paper shows the results of a research which sought to find answers to the main difficulties faced by students and teachers of the DIC course, in relation to the teaching and learning process. In order to obtain the data, questionnaires were applied to the students of the course and to the teachers who teach or have already taught this course on the Campus, as well as monitoring for a group of students. The results show the reality of DIC teaching and learning at Campus Januária and opens the door for discussions about this issue that covers not only the IFNMG, but also other higher education institutions in Brazil. Keywords: Differential and Integral Calculus. Learning Difficulties. Higher Education.